Analysis of Tc99m MDP Radiopharmaceuticals in the Spinal Areas of Breast Cancer Patients - Desty Anggita Tunggadewi; Syefira Lupita Azmi; Budi Santosa (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2022)
The aim of this study was to obtain doses in the spine of breast cancer patients. This dose is very important in pharmacy to determine the distribution of drugs in the body's organs, especially the spine. The data of this study came from the results of bone scintigraphy examinations which had known the value of the injection dose and the percentage of absorption in the spine. This research was conducted by simulating the biological half-life values for 3 hours, 4 hours, 5 hours, 6 hours, and 7 hours to find the total half-life which will produce a total decay constant that will be used in calculating spinal dose. The results obtained were the lowest mean dose in the spinal 0.680 ± 0.160 mCi when the decay constant had the highest value (biological half-life 3 hours) and the largest mean dose in the spinal 1.011 ± 0.238 mCi when the decay constant had the lowest value (biological half-life 7 hours). In the spine, the thoracic region is the area with the highest dose because it is located closest to the breast organs (breast cancer) so it will experience the highest damage/metastasis. Then the Tc99m MDP radiopharmaceutical absorbed into the thoracic region will be higher. By simulating the biological half-life, it is hoped that we can find the exact biological half-life for the absorbed dose